PENENTUAN KECEPATAN PENGENDAPAN UNTUK MERANCANG UNIT PENGENDAP NATRIUM BENTONIT - Siti Isnijah S.P.; Tasrif Tasrif; Nuryatini Nuryatini (Research Center for Chemistry - LIPI, 1997)
One step of producing paint additive from bentonite is to change Ca-beruonite into Na-bentonite. It applied ion-exchange process by using saturated solution of NaCl. Purification of product was done by washing to remove excess of salt. Nabentonite in production capacity of 40 kg could be separated from water by decantation. Observing the performance of precipitation rate of No-bentonite gave technical data for designing of precipitation unit. The precipitation of Na-bentonite in laboraroty scale was conducted using glass columns with diameter of 2.7 cm; 4.7 cm; 6.2 cm and 11.5 cm respectively. Height of slurry in column was varied in a range of 0.1 m ; 0.2 m ; 0.4 m and 1.0 m. The higher